The scientific revolution and its role in the transition to sustained economic growth - Sibylle H. Lehmann-Hasemeyer; Klaus Prettner; Paul Tscheuschner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2020)
We propose a Unified Growth model that analyzes the role of the Scienti fic Revolution in the takeoff to sustained modern economic growth. Basic scientific knowledge is a necessary input in the production of applied knowledge, which, in turn, fuels productivity growth and leads to rising incomes. Eventually, rising incomes instigate a fertility transition and a takeoff of educational investments and human capital accumulation. In regions where scientific inquiry is severely constrained (for religious reasons or because of oppressive rulers), the takeoff to modern growth is delayed or might not occur at all. The novel mechanism that we propose for the latent transition towards the takeoff could contribute to our understanding of why sustained growth emerged first in Europe.
urn:nbn:de:bsz:100-opus-17442
Keywords: O11; O31; O33; O41; 330; Scientific Revolution; Industrial Revolution; Basic Science; Applied Science; Takeoff to Sustained Growth; Unified Growth Theory